Muqtatafat Min Al Sy’ir Al Jahili - Ahmad H.Osman, Rahmah; Mahmud, Murni; Mohd Ghalib, Mohd Feham; Ahmed Mahmoud, Ahmed Ragheb (2017)
The copyright introduces the teaching materials on classical Arabic poetry to non-native speakers